2020
DOI: 10.1186/s12962-020-00208-w
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of dapagliflozin versus metformin in Chinese patients whose diabetes is inadequately controlled with diet and exercise

Abstract: Background: To investigate the long-term economic outcome of dapagliflozin versus metformin in Chinese patients with type 2 diabetes mellitus (T2DM) whose diet and exercise have not provided sufficient glycemic control.Methods: An economic analysis of dapagliflozin versus metformin was conducted by using the Chinese Outcomes Model for T2DM with a time horizon of lifetime, which was developed and validated based on the Chinese population. The efficacy data of lowering HbA1c of dapagliflozin and metformin was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Several CE studies have tested whether dapagliflozin could be cost-effective compared with other treatment strategies for diabetes patients in China, but their conclusions were not consistent. 10,11 However, there was no CE study for dapagliflozin in HFrEF patients. Given that the combination of dapagliflozin has potential for widespread use among HFrEF patients, decision makers must determine whether the extra benefit with dapagliflozin is worth the additional costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several CE studies have tested whether dapagliflozin could be cost-effective compared with other treatment strategies for diabetes patients in China, but their conclusions were not consistent. 10,11 However, there was no CE study for dapagliflozin in HFrEF patients. Given that the combination of dapagliflozin has potential for widespread use among HFrEF patients, decision makers must determine whether the extra benefit with dapagliflozin is worth the additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…Cost‐effectiveness (CE) analysis (CEA) is a useful approach to assess medication value by quantifying and comparing the therapy cost and effectiveness of different treatment strategies. The CE of dapagliflozin (compared with different treatment strategies) for patients with type 2 diabetes mellitus was not consistent in China 10,11 . Additionally, there is no study about the CE of dapagliflozin among HFrEF patients in China.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The analysis was carried out by using a mathematical model, which could annually track the T2DM progression from prediabetes (Figure 1). Once the patients developed T2DM, the disease course would be projected by using the Chinese Outcomes Model for T2DM (COMT) [8,12,13]. This validated diabetes policy analysis model would track simultaneously several critical diabetic macro-and microvascular complications for one hypothetical T2DM patient, including myocardial infarction (MI), congestive heart failure (CHF), cardiovascular disease (CVD), stroke, blindness, end-stage renal disease (ESRD), clinical neuropathy, foot ulcer, and minor and major amputation.…”
Section: Methodsmentioning
confidence: 99%
“…Lifestyle intervention has been advocated to decrease the risk of T2DM in prediabetic subjects, which could reduce 3% absolute risk compared with no prevention [6][7][8]. The Da Qing Diabetes Prevention Study found that a 6-year lifestyle intervention program for those with impaired glucose tolerance (IGT) reduced the 17.3% cumulative incidence of diabetes (hazard ratio (HR): 0.55, 95% CI: 0.40-0.76) during the 23-year follow-up period [9].…”
Section: Introductionmentioning
confidence: 99%